DISTRIBUTION AND BEHAVIOUR OF DISSOLVED AND PARTICULATE Pb AND Zn IN JENEBERANG ESTUARY, MAKASSAR - . Najamuddin; Tri Prartono; Harpasis s. Sanusi; I Wayan Nurjaya (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2016)
ABSTRACTDissolved and particulate heavy metals play a role in geochemical cycle as an agent in adsorption-desorption, deposition-resuspension, and dispersion mechanisms of heavy metals in water environment. The objectives of this research were to determine the distribution and behaviour of dissolved and particulate heavy metals Pb and Zn in different seasons (west and east seasons) at Jeneberang Estuary of Makassar. Concentrations of Pb and Zn were analysed using Atomic Adsorption Spectrophotometry based on APHA, AWWA, WEF (2005). The concentration of dissolved Pb in the riverine, estuarine, and marine waters were in the range (average) of <0.002 mg/L (below detectable limit), 0.013-0.144 mg/L (0.047 mg/L), 0.016-0.198 mg/L (0.079 mg/L); and the concen-tration of dissolved Zn were in the range (average) of <0.002 mg/L (below detectable limit), <0.002-0.014 mg/L (0.005 mg/L), <0.002-0.083 mg/L (0.017 mg/L). Meanwhile, the concentration of parti-culate Pb were in the range (average) of 1.807-2.569 mg kg-1 (2.215 mg kg-1), 0.521-1.272 mg kg-1 (0.911 mg kg-1), 0.465-2.182 mg kg-1 (1.033 mg kg-1), and the concentration of particulate Zn were in the range (average) of 19.151-90.942 mg kg-1 (51.710 mg kg-1), 16.999-63.059 mg kg-1 (31.694 mg kg-1), 19.439-80.283 mg kg-1 (45.554 mg kg-1) in the riverine, estuarine and marine waters, respecti-vely. Behaviour of dissolved heavy metals Pb and Zn showed that the concentrations tended to increase (desorption) along the gradient of high salinity as a result of the higher heavy metals input from coastal region than that riverine regimes.Keywords: distribution, behaviour, dissolved, particulate, heavy metal, Jeneberang Estuary